Kinematics and Motion Modeling of a Robotic Arm using MATLAB Program - Hemhirun, Surachai; Tanpradit, Ditthaphat (Srinakharinwirot University Engineering Journal, 2022)
This research aimed to study kinematics and motion modeling of a robot arm using MATLAB program for the identification of the end-effector (EE) coordinates. The robot arm has a 4 degree-of-freedom (DOF) which was created by a 3-D modeling program. After that, the kinematics model was analyzed, and the program was simulated by MATLAB/Simulation program. The test consisted of two parts. The first part is to validate the kinematics model while the second part is to simulate continuous motion by writing an English alphabet. The test method uses the display of a robotic arm from a 3-D model compared with the kinematic model. the results showed that the kinematic calculation of the model revealed the EE coordinates, and all the joint angle values were accurate, causing the work area along x, y, and z-axes in the range of 52 to 239, -234 to 234, and 0 to 228 mm. respectively. The simulation showed correct and perfect writing. In addition, it was found that the round-off of the joint angle value affects the error in specifying the coordinates of the EE.